(untitled) (Fiep Bulletin - online, 2025)
This study highlights the importance of dance in the school context, particularly in Physical Education classes, focusing on teaching urban dances in the 6th and 7th grades of elementary school, according to the guidelines of the National Common Curricular Base – BNCC (Brazil, 2018). Initially, dance is emphasized to promote the integral development of students, covering physical, emotional, social and cultural aspects. Through movement, dance allows the expression of feelings and reflections on the body and the surrounding environment, helping to understand how the body functions. Urban dances, which emerged in the United States in a scenario of social marginalization, are explored as bodily practices that combine movement, rhythm and cultural meaning, contributing to identity formation and respect for diversity. Methodologically, the qualitative research was based on a bibliographic review, highlighting the relevance of dance as an integrative and inclusive element in classes. The results demonstrate that dance stimulates motor skills, creativity, social reflection and cultural appreciation, aligning with the proposals of the BNCC. It is concluded that the integration of urban dances into the school curriculum encourages sociocultural debates, expands students’ repertoire and reinforces the importance of Physical Education as a promoter of comprehensive education.